AN ANALYSIS OF ILLOCUTIONARY ACTS PERFORMED IN DONALD TRUMP’S VICTORY SPEECH IN THE UNITED STATES ELECTION 2016 - Anisa Nur Azizah; Dinar Alpiah (IKIP Siliwangi, 2018)
This study deals with an analysis of illocutionary act in Donald Trump’s utterances in his Victory Speech in the United States election 2016. The objectives of this study are to identify types of illocutionary act used by Donald Trump and to identify the most dominant type of illocutionary act. The data was taken from www.youtube.com.In this study, the researchers applieddocumentation technique in collecting the dataand the descriptive qualitative method was used to analyze the data. The researchers used Yule’s theory forthe types of illocutionary acts.The findings showed that there are five types of illocutionary acts found in this study including declarative (DC) occurs (2), representative (RP) occurs (46), expressive (EV) occurs (38), directive (DR) occurs (7), and commissive (CM) occurs (24).The researchers also find mostly performs in Donald Trump’s utterances in Victory Speech is, and informing his victory and his plan as the new representative act which is refers tostating, asserting, predicting, retelling president of United States to the audience. Keywords:speech acts, illocutionary acts, victory speech.